Assessment of occupational safety and health management system OHSAS 18001 on safety performance at How Mine - Mpofu, Lovemore (Midlands State University, 2018)
Occupational Health Assessment Series (OHSAS) 18001 was recognized internationally as an auditable system to manage safety and health risks at workplaces since 1999. The purpose of the study was to assess the impact of OSHAS 18001 management system on safety performance at How Mine, a gold mining company in Zimbabwe. The objectives of the study were to analyze the occupational accidents before and after the adoption of OHSAS 18001 and to evaluate occupational injury frequency rate and injury severity rate. As well as assessment of safety practices at the mine, before and after adoption of OHSAS 18001 were done. The research was exploratory in nature and employed the cross sectional survey design. The sample size used was of 100 participants who had worked for the mine for a period of one year and above on a continuous basis. Stratified random sampling was used due to the diversity of activities at How mine. Primary and secondary information was obtained through interviews, questionnaires and review of records at the mine. Records analyzed included accidents reports, injuries treated at the clinic, workers compensation claims among others. Correlation and regression analysis were used to test relationships of the independent and dependent variables. The study found out that the trend of accidents at How mine declined by 90% from 2007 to 2016. Occupational lost time injury frequency rate declined from a high of 14 to 0.3 and injury severity rate declined from 15 to 0.1. Workplaces are considered safe when the injury frequency rate and injury severity rate are below 1.Workers compensation claims for those injured on duty dropped from a high of 31 to 2 for the period covered in the study. The study concluded that safety performance improved as measured by lagging indicators, such as lost time injuries, injury frequency rate and injury severity rate. The study found out that proactive activities increased during the period reviewed. OHSAS 18001 improved safety performance at How mine in Zimbabwe.